Rapid Identification of Mycobacterium tuberculosis Complex Using Mass Spectrometry: A Proof of Concept - Robinne, Simon; Saad, Jamal; Morsli, Madjid; Hamidou, Zelika Harouna; Tazerart, Fatah; Drancourt, Michel; Baron, Sophie Alexandra (Frontiers in Microbiology, 2022)
Mycobacteria that form the Mycobacterium tuberculosis complex are responsible for deadly tuberculosis in animals and patients. Identification of these pathogens at the species level is of primary importance for treatment and source tracing and currently relies on DNA analysis, including whole genome sequencing (WGS), which requires a whole day. In this study, we report the unprecedented discrimination of M. tuberculosis complex species using matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF-MS), with WGS as the comparative reference standard. In the first step, optimized peptide extraction applied to 36 isolates otherwise identified in five of the 11 M. tuberculosis complex variants by WGS yielded 139 MALDI-TOF spectra, which were used to identify biomarkers of interest that facilitate differentiation between variants. In a second step, 70/80 (88%) other isolates were correctly classified by an algorithm based on specific peaks. This study is the first to report a MALDI-TOF-MS method for discriminating M. tuberculosis complex mycobacteria that is easily implemented in clinical microbiology laboratories.